An update on the clinical pharmacology of methylphenidate: therapeutic efficacy, abuse potential and future considerations. Issue 8 (2nd August 2020) - Shellenberg, Thomas P.; Stoops, William W.; Lile, Joshua A.; Rush, Craig R.
ABSTRACT: Introduction: Methylphenidate remains a first-line medication for treating ADHD in children and adults. However, its behavioral pharmacological similarities to methamphetamine and cocaine have historically created concern for its potential as a drug of abuse. In September 2019, the FDA published a docket requesting comments for the development of abuse deterrent formulations for CNS stimulants, emphasizing the abuse of methylphenidate as a public health concern. Areas covered: We conducted a narrative review of research on the clinical pharmacology, therapeutic efficacy, and abuse potential of methylphenidate. Expert opinion: Several studies indicate that methylphenidate has at least some abuse potential. Methylphenidate, amphetamine, methamphetamine, and cocaine overlap in their subjective, reinforcing, and discriminative stimulus effects. Regardless, methylphenidate remains an efficacious treatment for ADHD in children and adults when properly adhered to, especially when paired with non-pharmacological treatments. The development of abuse deterrent formulations of methylphenidate is warranted.